SIADH, a Rare Complication Postcarotid Endarterectomy – Case Report and Review of Literature - Kovidh Chittibomma; Jithin Jagan Sebastian; Sairam Subramanian (Indian Journal of Vascular and Endovascular Surgery)
Severe hyponatremia, postcarotid endarterectomy (CEA) is a rare phenomenon. Several physiological conditions lead to hyponatremia post-CEA. We describe the case of an 83-year-old hypertensive who developed severe hyponatremia after right CEA for symptomatic carotid artery stenosis. He developed symptoms of severe hyponatremia on postoperative day 4, before discharge, with a serum sodium level of 112 mmol/L. He was investigated and found to have diuretic-induced hyponatremia alongside syndrome of inappropriate antidiuretic hormone secretion. The symptoms were recognized early, and both causes were treated, leading to improvements in sodium levels and preventing further deterioration. The patient was discharged on an ADH receptor antagonist with no recurrence of symptoms during follow-up. There have been four similar cases reported in the literature, which have been reviewed in comparison to the present case. Severe hyponatremia post-CEA presents after 24 h of surgery, and awareness helps early diagnoses and prevents hyponatremia-related readmission and patient morbidity.